Pembentukan Karakter Siswa Di Smp Muhammadiyah 1Kartasura Tahun Pelajaran 2015 / 2016 - Nasrudin, Nasrudin; , Drs. Zaienal Abidin, M.Pd; , Drs. Arif Wibowo, M.Ag (2017)
SMP Muhammadiyah 1 Kartasura is one of educational institutions with an Islamic nuance which is hoped to be exist in order to create an Islamic generation who are strong and master knowledge in order to respond the era challenge which is getting more and more complex. Besides, the forming of character building of the students is appropriate to what dreamt by the teacher that is to create smart intellectual generation with a good character. From this background, the problem statement is how the character building of the students in SMP Muhammadiyah 1 Kartasura in the academic year of 2015/2016 is. Meanwhile, the benefits of this research are: to add knowledge on the importance of character education. For the teachers, it can be made as an evaluation material in increasing the self-quality in the moral problem, therefore; it can be made as the good model for the students. For the school, it can be made as an input in increasing the coaching on the teachers especially in the moral problem. For the writer, it can be made as a self-evaluation material because the writer will become a teacher in future so that the writer should always do betterment in moral. This research is a field research. The methods of data collection used are interview, observation, and documentation. Meanwhile, the method of data analysis is descriptive qualitative. Based on the research, it is found that the character building of the students in SMP Muhammadiyah 1 Kartasura runs well. It is proved by the improvement of the achievement as well as the students' moral. As the example, the teacher of fiqh has been able to coach and direct the students in the worship, conducting dhuha and zhuhur praying together and on time everyday and giving donation (infaq) every Friday. Also, the teacher of Akhlaq had been able to direct the students to always behave good. It could be seen that the students behave politely and well mannered to the teachers and the employees. The teacher of tahfizh and Qur'an Hadith had been able to increase the students' ability in reciting and writing al Qur'an well. It is conducted by the students in the extra Reading-Writing Qur'an which is held every Thursday. Therefore, viewed from the competency which had been conducted, in building the students' character, there is no obstacle. Meanwhile, the strategies used in building the characters are moral knowing, moral feeling, and moral doing. Moral knowing: is the first stage in the character education aiming at orientating to the mastery of moral values. Moral feeling: is intended to grow the sense of love and need the moral values. Moral doing is the top of success the moral education where in the students practice the moral values in the daily life.